Association of common mental disorders and related multimorbidity with subsequent labor market marginalization among refugee and Swedish-born young adults - Chen, Jiaying; Mittendorfer-Rutz, Ellenor; Berg, Lisa; Nørredam, Marie; Sijbrandij, Marit; Klimek, Peter (Frontiers in Public Health, 2023)
Background Common mental disorders (CMDs), multimorbidity, and refugee status are associated with poor labor market outcome. Little is known about how these factors interact in young adults. Objective We aimed to i) investigate whether the association of CMDs and multimorbidity with labor market marginalization (LMM) differs between refugee and Swedish-born young adults and ii) identify diagnostic groups with particularly high risk for LMM. Methods This longitudinal registry-based study included individuals aged 20–25 years followed from 2012 to 2016 in Sweden (41,516 refugees and 207,729 age and sex-matched Swedish-born individuals). LMM was defined as granted disability pension (DP) or > 180 days of unemployment (UE). A disease co-occurrence network was constructed for all diagnostic groups from 2009 to 2011 to derive a personalized multimorbidity score for LMM. Multivariate logistic regression was used to estimate odds ratios of LMM in refugee and Swedish-born youth as a function of their multimorbidity score. The relative risk (RR, 95% CI) of LMM for refugees with CMDs compared to Swedish-born with CMDs was computed in each diagnostic group. Results In total, 5.5% of refugees and 7.2% of Swedish-born with CMDs were granted DP; 22.2 and 9.4%, respectively received UE benefit during follow-up. While both CMDs and multimorbidity independently elevated the risk of DP considerably in Swedish-born, CMDs but not multimorbidity elevated the risk of UE. Regarding UE in refugees, multimorbidity with the presence of CMDs showed stronger estimates. Multimorbidity interacted with refugee status toward UE (p < 0.0001) and with CMDs toward DP (p = 0.0049). Two diagnostic groups that demonstrated particularly high RR of UE were schizophrenia, schizotypal and delusional disorders (RR [95% CI]: 3.46 [1.77, 6.75]), and behavioral syndromes (RR [95% CI]: 3.41 [1.90, 6.10]). Conclusion To combat LMM, public health measures and intervention strategies need to be tailored to young adults based on their CMDs, multimorbidity, and refugee status.